Mozart Memberikan Hasil Indeks Apoptosis Lebih Rendah daripada Musik Pop, Religi dan Tanpa Pemberian Musik - Dian Sukmawati; Hermanto Tri Juwono; Widjiati Widjiati (FORIKES, 2020)
Background: Brain growth requires genetic potential for a conducive environment, low stress levels, stimulation and nutrition. Brain development during the fetal period in the two years of life firstly requires proper stimulation to increase intelligence. Classical music stimulation has been proven to be able to optimally improve brain function and human intellect. Other music that Indonesian people like is pop and religion. Maybe it is possible to pop and religious music can affect the development and growth of the fetal brain. Objective: Analyze the differences of the index of apoptosis Cerebrum and Cerebellum Rattus norvegicus newborn between those stimulated by Mozart, pop, religious music and not stimulated by music during pregnancy. Method: This study was post test only control group design. groups were randomly divided according to the treatment as stimulation of Mozart, pop, religious music and no music was given from the 10th day-gestation with an intensity of 65 dB in a soundproof box for one hour. When 19th day-gestation, Rattus norvegicus mothers were sacrificed then 3 Rattus norvegicus newborn from each mothers were selected and brain was taken to be made immunohistochemical preparations and counted the number of neuron cells apoptosis index. data were analyzed by comparison test with p